The terrace staircases of Douro River at the Pocinho and Barca d'Alva sectores (NE Portugal) records for the interpretation of the evolution of W Iberian during the Quaternary - Gomes, António (2015)
Since the second half of the last century geomorphological cartography in some reaches of the Lower river Tejo (Portugal) was undertaken (Martins, 1999; Cunha et al., 2008; Martins, et al., 2009; Martins, et al., 2010a). Up to six terraces were identifieds in reach I (Ródão), reach III (Abrantes) and reach IV (Vila Nova da Barquinha - Vila Franca de Xira.A resistant Palaezoic basement....